The missing piece of the upper mesopelagic carbon budget? Biomass, vertical distribution and feeding of aggregate-associated copepods at the PAP site. (February 2020) - Koski, Marja; Valencia, Bellineth; Newstead, Rebekah; Thiele, Christine
Highlights: Aggregate-associated copepods can have a large influence on the attenuation of the vertical flux. Particle degradation by these copepods can equal the surplus in the epipelagic carbon. Biomass of M. norvegica and Oncaea spp. is variable both in time and in space. Understanding their distribution is needed to predict the changes in the biological pump. Abstract: Although zooplankton are recognized as important consumers of marine snow, our knowledge of the contribution of the small (<1 mm) zooplankton to the degradation of sinking particles, and therefore on the efficiency of the biological pump, is limited. To estimate the marine snow consumption by small aggregate-feeding copepods, we measured the daily changes in biomass and vertical distribution of the harpacticoid Microsetella norvegica and the poecilostomatoid Oncaea spp. over a period of 10 days and combined these with estimates of their feeding and respiration rates. We estimated copepod feeding rates in multiple ways, using: gut chlorophyll content, maximum ingestion rates from functional responses on two types of aggregates, carbon demand based on the respiration measurements, and egg production rates. Microsetella norvegica and Oncaea spp. biomass levels varied > 2-fold between sampling dates for geographically-close sampling stations. Microsetella norvegica resided mainly in the surface layer, at or immediately below the fluorescence peak, while Oncaea spp. was typically deeper. Microsetella norvegica fed actively on Trichodesmium filaments, with a maximum ingestion rate of ca. 0.11 µg C ind. −1 d −1, while their ingestion of detritus aggregates was low. Feeding on Trichodesmium was reflected in their gut chl- a content, which was high for M. norvegica at all but one sampling time. In contrast, Oncaea spp. had significantly lower gut chl- a content and may have been feeding on other types of aggregates. Respiration of both copepods was variable and as much as 0.08 µL ind. −1 h −1 for M. norvegica and 0.04 µL ind. −1 h −1 for Oncaea spp. Based on individual biomass, vertical distribution, and carbon demand, aggregate-associated copepods could degrade up to 79 ± 33 mg C m −2 d −1, a value similar to the surplus in the epipelagic carbon budget of the area. This large degradation rate demonstrates that zooplankton < 1 mm can have a large influence on the vertical flux and that the factors controlling their abundances and feeding rates should be high in the priority list of future zooplankton studies.